Indoleamine 2,3-dioxygenase-1 expression in non-small-cell lung cancer: analyses of prevalence, clinical correlations and prognostic impact in 2 large patient cohorts - Agustoni, Francesco; Yu, Hui; Ellison, Kim; Smith, Derek; Mitchell, Paul; Rivalland, Gareth; Dziadziuszko, Rafal; Gao, Dexiang; Ren, Shengxiang; Rivard, Christopher J.; San Millan, Inigo; Corallo, Salvatore; et al. (Frontiers in Immunology, 2025)
BackgroundIndoleamine 2,3-dioxygenase-1 (IDO-1) is a cytosolic enzyme involved in the catabolism of tryptophan. IDO-1-related immune suppression is due to decreased tryptophan availability and to the generation of tryptophan metabolites, culminating in substantial suppression of T-lymphocytes. Here we investigate IDO-1 expression in 2 cohorts of non-small-cell lung cancer (NSCLC) specimens, both in tumor cells and in immune infiltrate, with correlation of IDO-1 to PD-L1 expression, clinical patient demographics and outcomes.MethodsEvaluation first utilized an exploratory cohort of 259 NSCLC samples obtained from 122 patients followed by a second validating cohort of 1,200 NSCLC samples obtained from 437 patients. All tumor samples were collected from patients who underwent surgical lung resections. IDO-1 expression was evaluated by immunohistochemistry (IHC). Correlations were assessed using Spearman and Kendall tests. A Cox proportional hazards (PH) model was used to assess if overall survival (OS) was associated with IDO-1 positivity in univariate and multivariable settings.ResultsIn the validating cohort of 437 patients IDO-1 expression was positive in 111 (25.4%) with an H-Score ≥ 1. IDO-1 expression was determined to be greater in tumor immune infiltrate, with 406 patients (93.8%) determined as positive. Both continuous and binary versions of tumor H-Score showed a significant positive correlation with the amount of tumor immune infiltrate (0.1806 and 0.1698, p < 0.0001). None of the analyzed variables (age, sex, histology, stage, EGFR, KRAS and PD-L1 status) were found to display a significant correlation with IDO-1 positivity in tumor and immune cells. IDO-1 positivity in tumor cells was found to be significantly associated with OS in the univariate setting and in the multivariable model [P-value = 0.009 and 0.021, respectively; HR: 0.72 (95% CI: 0.55-0.95)]. IDO-1 positivity in immune cells was found to be significantly associated with OS in the univariate setting and was borderline significant in the multivariable model [P-value = 0.006 and 0.053; HR: 0.798 (95% CI: 0.635-1.003)].ConclusionOur results suggest a prognostic role of IDO-1 protein expression in NSCLC tumor and immune cells independent of EGFR, KRAS AND PD-L1 expression, and should be explored as a predictive biomarker in clinical studies with IDO-1 targeted therapies.